High-strength aluminum alloy profile for automobile threshold beam and preparation method of high-strength aluminum alloy profile
By optimizing the chemical composition and process flow of aluminum alloy materials, forming fine isometric grains and co-categorical interfaces, the shortcomings of automobile threshold beam materials in impact and corrosion are solved, and high strength, high elongation and high corrosion resistance are achieved. effect.
Patent Information
- Application Number
- CN202411689096.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing automotive sill beam materials have shortcomings in impact and corrosion, which are difficult to meet the high strength, high elongation and high corrosion resistance requirements of new energy vehicles.
Aluminum alloy materials with specific chemical compositions, including Si, Mg, Cu, Mn, Cr, Zn, Zr and Ti elements, are formed through smelting, homogenization treatment, extrusion molding, online quenching, stretching and double-stage aging processes. The fine equiaxed grains and a co-equivalent interface improve mechanical properties and corrosion resistance.
It realizes the high tensile strength, yield strength and hardness of aluminum alloy materials, meets the mechanical performance requirements of the threshold beam of new energy vehicles, and improves the corrosion resistance and toughness of the materials.
Smart Images

Figure CN119194187A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloy profiles, and in particular to a high-strength aluminum alloy profile for an automobile door sill beam and a preparation method thereof. Background Art
[0002] With the rapid development of the automobile industry, the collision safety performance of automobiles has received more and more attention, which is of great significance to protecting the life and property of drivers and passengers. At present, the automobile industry has gradually developed in the direction of lightweight automobiles, especially for new energy vehicles. Lightweight is even more important for the cruising range of new energy vehicles. In order to achieve lightweight, aluminum alloy has become the main material for automobile manufacturing. When a car is hit from the side, the sill beam is subjected to a large impact force and deforms under the impact to absorb energy, thereby protecting the safety of drivers and passengers. In addition, it also plays the role of ensuring the safety of the battery pack shell on new energy vehicles, avoiding the risk of failure and fire caused by deformation of the battery pack shell due to large deformation of the bottom plate during side collision, thereby squeezing the battery module. This requires the sill beam to have high strength and high elongation; and because there is wading at this position of the sill beam, the sill beam is also required to have high corrosion resistance. At present, high-strength steel and 6 series aluminum alloy are usually used in the position of the door sill beam, but high-strength steel is heavy and has poor corrosion resistance. Therefore, in order to meet the market demand of the automotive industry, it is urgent to develop an aluminum alloy material with high strength, high elongation and high corrosion resistance. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a high-strength aluminum alloy profile for an automobile door sill beam and a preparation method thereof.
[0004] The technical solution adopted by the present invention is: A high-strength aluminum alloy profile for automobile door sill beams comprises the following metal element components in percentage by mass: Si 0.25-0.35%, Mg 1.2-1.6%, Cu 0.2-0.5%, Mn 0.4-0.6%, Cr 0.1-0.2%, Fe≤0.05%, Zn 4.0-4.5%, Zr 1.0-1.5%, Ti 0.05-0.1%, and the balance is Al and unavoidable impurities.
[0005] Furthermore, the metal element components include the following mass percentages: Si 0.25-0.35%, Mg 1.4-1.6%, Cu 0.2-0.5%, Mn 0.4-0.6%, Cr 0.15-0.2%, Fe≤0.05%, Zn 4.3-4.5%, Zr1.3-1.5%, Ti 0.08-0.1%, and the balance is Al and unavoidable impurities.
[0006] Furthermore, the aluminum alloy profile has a tensile strength of ≥470 MPa, a yield strength of ≥430 MPa, and an elongation of ≥16%.
[0007] Furthermore, the method includes the following steps: melting according to alloy composition → casting aluminum rods → homogenization → extrusion molding → online quenching → stretching → sawing → artificial aging → testing whether mechanical properties meet the requirements.
[0008] Furthermore, in the smelting process, the alkali metals in the aluminum liquid after refining need to be controlled to be K≤0.0002%, Na≤0.0002%, and Ca≤0.0005%.
[0009] Furthermore, the homogenization process is as follows: the homogenization temperature is 460±3°C, the heat preservation time is 36±0.5h, and the homogenization is followed by natural cooling to room temperature.
[0010] Furthermore, the specific parameters of the extrusion molding process are: aluminum rod temperature is 500±10°C, extrusion barrel temperature is 440±20°C, mold temperature is 480±15°C, mold heating time is 5~24h, extrusion rod speed is 1.0~1.5mm / s, traction speed is 1.2~1.6m / min, and outlet temperature is 515~540°C.
[0011] Furthermore, in the online quenching process, online water quenching is adopted, and the temperature after quenching is ≤60°C.
[0012] Furthermore, in the stretching process, the stretching rate is 2%.
[0013] Furthermore, the artificial aging process adopts a double-stage aging process, the first stage aging is 105±5℃×8h, and the second stage aging is 155±5℃×8h.
[0014] The beneficial effects of the present invention are: (1) The present invention provides a high-strength aluminum alloy profile for automobile door sill beams and a preparation method thereof. By adding high contents of Zr and Cr elements, the Zr element forms an Al3Zr dispersed phase in the aluminum alloy and acts as a heterogeneous core, promoting the nucleation of grains on these heterogeneous cores during solidification, thereby obtaining fine equiaxed grains, and further improving the mechanical properties of the aluminum alloy material; at the same time, during heat treatment and deformation, the Al3Zr dispersed phase formed by the Zr element can also hinder the movement of grain boundaries, thereby inhibiting the recrystallization process, helping to maintain the stability of the mechanical properties of the alloy at high temperatures, and preventing the performance degradation of the material under high temperature environments; in addition, the combined action of Zr and Cr elements can form a coherent interface between the dispersed phase and the matrix, thereby improving the hardenability, toughness and corrosion resistance of the alloy; (2) The present invention also controls the quenching method and aging system. By online water quenching, the coarse grain ring of the extruded product is reduced and the grain size is increased, thereby obtaining higher hardness and strength. In addition, the present invention also adopts a double-stage aging process. During the double-stage aging process, excess Zn forms a MgZn2 strengthening phase. The solubility of the MgZn2 phase in the alloy decreases sharply with decreasing temperature, providing a strong aging hardening ability. A portion of Zn remains in the alloy. Since zinc atoms are smaller than aluminum atoms, they can form a lattice dislocation structure in the aluminum lattice, thereby limiting the movement of dislocations and grain boundaries, enhancing the strengthening effect of grain boundaries, and further improving the strength and hardness of the aluminum alloy. The tensile strength reaches above 470MPa, the yield strength reaches above 430MPa, and the hardness reaches above 130HB, so that it meets the mechanical property requirements of the threshold beam of new energy vehicles. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 This is a metallographic photograph of an aluminum alloy profile sample prepared in Example 8 of the present invention using online water quenching; Figure 2 It is a metallographic photograph of the aluminum alloy profile sample prepared in Example 8 of the present invention using online water mist quenching. DETAILED DESCRIPTION
[0017] The present invention provides a high-strength aluminum alloy profile for an automobile door sill beam and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0018] A high-strength aluminum alloy profile for automobile door sill beams comprises the following metal element components in percentage by mass: Si 0.25-0.35%, Mg 1.2-1.6%, Cu 0.2-0.5%, Mn 0.4-0.6%, Cr 0.1-0.2%, Fe≤0.05%, Zn 4.0-4.5%, Zr 1.0-1.5%, Ti 0.05-0.1%, the balance being Al and inevitable impurities, and the content of each impurity element does not exceed 0.04%, and the total amount of impurities does not exceed 0.10%; preferably, Mg 1.4-1.6%, Cr 0.15-0.2%, Zn 4.3-4.5%, Zr 1.3-1.5%, Ti 0.08-0.1%, and the balance being Al and inevitable impurities.
[0019] The present invention limits and optimizes the chemical composition of the high-strength aluminum alloy profile for automobile door sill beams, and mainly adds high-content Zr and Cr elements. Zr elements form Al3Zr dispersed phases in aluminum alloys. These dispersed phases act as heterogeneous cores to promote the nucleation of grains on these cores during solidification, thereby obtaining fine equiaxed grains. The fine grain structure can significantly improve the mechanical properties of the material, including strength and toughness; at the same time, during heat treatment and deformation, the Al3Zr dispersed phases formed by Zr elements can hinder the movement of grain boundaries, thereby inhibiting the recrystallization process, which helps to maintain the mechanical property stability of the alloy at high temperatures and prevent the performance degradation of the material under high temperature environments; in addition, the combined action of Zr and Cr elements can form a coherent interface between the dispersed phase and the matrix, thereby improving the hardenability, toughness and corrosion resistance of the alloy; in addition, the present invention also adds a relatively high content of Mn elements, which can improve the corrosion resistance while improving the strength of the aluminum alloy.
[0020] A preparation method of a high-strength aluminum alloy profile for an automobile door sill beam comprises the following steps: melting according to alloy composition → casting aluminum rods → homogenization → extrusion molding → online quenching → stretching → sawing → artificial aging → testing whether mechanical properties meet requirements.
[0021] In the feeding and smelting process, the aluminum ingot is a remelting aluminum ingot with a purity of 99.85%, and other alloy elements are high-purity metals. The aluminum liquid that meets the requirements is obtained by melting in a smelting furnace, slag removal, alloy addition, slag removal, transfer to a refining furnace, slag removal, refining, slag removal, temperature adjustment, grain refinement, SNIF online degassing, and CFF filtration. In addition, in this process, online degassing is performed three times and filtering is performed twice to ensure that the alkali metal K in the aluminum liquid is ≤0.0002%, Na ≤0.0002%, and Ca ≤0.0005% after refining in the refining furnace; and then it is cast. The present invention can further improve the corrosion resistance by strictly controlling the alkali metal content, and can also prevent the formation of "sodium brittleness", pinholes and broken belts, thereby greatly improving the product yield.
[0022] In the homogenization process, the homogenization treatment is carried out at 460°C × 36 hours, the temperature is allowed to deviate by ±3°C, and the time is allowed to deviate by 30 minutes. After the homogenization treatment is completed, it is cooled to room temperature by natural cooling.
[0023] In the extrusion molding process, the temperature of the aluminum rod is 500±10℃, the temperature of the extrusion barrel is 440±20℃, the temperature of the mold is 480±15℃, the mold heating time is 5~24h, the extrusion rod speed is 1.0~1.5mm / s, the traction speed is 1.2~1.6m / min, and the outlet temperature is 515~540℃. In addition, in order to improve the yield, the barrel must be cleaned after every 80 aluminum rods are extruded.
[0024] In the online quenching process, online water quenching is used to effectively avoid profile deformation, and the temperature after quenching is ≤60℃.
[0025] In the stretching process, the stretching rate is 2%, and the cut to length is performed after the operation is completed.
[0026] In the artificial aging process, a double-stage aging process is adopted, with the first stage aging at 105±5℃×8h and the second stage aging at 155±5℃×8h.
[0027] In the above-mentioned preparation method of aluminum alloy profile, the mechanical properties of the threshold beam are mainly regulated by controlling the online quenching process and the aging process. The present invention utilizes online water quenching to reduce the coarse crystal ring of the extruded product, and the grains are fine and the grain size is large, so that higher hardness and strength can be obtained. At the same time, the aluminum alloy is very sensitive to quenching and cooling, and a strengthening phase will precipitate in the air in a very short time, affecting the strengthening effect. Therefore, the present invention adopts online water quenching to ensure that the supersaturated solid solution is fixed and not decomposed, and prevents the precipitation of the strengthening phase, which affects the performance of subsequent artificial aging. In addition, the present invention also adopts a two-stage aging process. During the two-stage aging process, excess Zn forms a MgZn2 strengthening phase. The solubility of the MgZn2 phase in the alloy decreases sharply with the decrease of temperature, providing a strong aging hardening ability. A part of Zn remains in the alloy, and because zinc atoms are smaller than aluminum atoms, they can form a lattice dislocation structure in the aluminum lattice, thereby limiting the movement of dislocations and grain boundaries, enhancing the strengthening effect of grain boundaries, and further improving the strength and hardness of the aluminum alloy.
[0028] Example 1
[0029] The present embodiment provides a high-strength aluminum alloy profile for an automobile door sill beam, comprising the following metal element components in percentage by mass: Zn 4.0%, Mg 1.2%, Zr 1.0%, Cr 0.1%, Ti 0.05%, Cu 0.2%, Mn 0.4%, Si 0.25%, Fe≤0.05%, and the remainder is Al.
[0030] The preparation method of the above-mentioned high-strength aluminum alloy profile for automobile door sill beam includes the following steps: melting according to alloy composition → casting aluminum rods → homogenization treatment → extrusion molding → online quenching → stretching → sawing → artificial aging → testing whether the mechanical properties meet the requirements.
[0031] Specifically, in the above-mentioned feeding and smelting process, the aluminum ingot is an aluminum ingot for remelting with a purity of 99.85%, and other alloy elements are made of high-purity metals. The aluminum liquid is melted in a smelting furnace - slag-added - slag-transferred to a refining furnace - slag-refined - slag-temperature adjustment - grain refinement - SNIF online degassing - CFF filtration to obtain aluminum liquid that meets the requirements; in addition, in this process, online degassing is performed three times and filtration is performed twice to ensure that the alkali metal K≤0.0002%, Na≤0.0002%, and Ca≤0.0005% in the aluminum liquid after refining in the refining furnace; and then cast to obtain a φ228mm aluminum rod.
[0032] In the above homogenization process, the homogenization process is carried out at 460°C × 36 hours, the temperature is allowed to deviate by ±3°C, and the time is allowed to deviate by 30 minutes. After the homogenization process is completed, it is cooled to room temperature by natural cooling.
[0033] In the above extrusion molding process, the aluminum rod temperature is 505°C, the extrusion barrel temperature is 440°C, the mold temperature is 485°C, the mold heating time is 10h, the extrusion rod speed is 1.2mm / s, the pulling speed is 1.4m / min, and the outlet temperature is 530-540°C. In addition, in order to improve the yield, the barrel cleaning operation must be carried out every 80 aluminum rods extruded.
[0034] In the above-mentioned online quenching process, online water quenching is adopted, which can effectively avoid deformation of the profile, and the temperature after quenching is ≤60°C.
[0035] In the above stretching process, the stretching rate is 2%, and the steel is sawn to length after the operation is completed.
[0036] In the above artificial aging process, a double-stage aging process is adopted, the first stage aging is 105±5℃×8h, and the second stage aging is 155±5℃×8h.
[0037] Example 2
[0038] The difference between this embodiment and embodiment 1 is that the high-strength aluminum alloy profile for the automobile door sill beam of this embodiment includes the following metal element components in percentage by mass: Zn 4.5%, Mg 1.6%, Zr 1.5%, Cr 0.2%, Ti 0.1%, Cu 0.5%, Mn 0.6%, Si 0.35%, Fe≤0.05%, and the balance is Al.
[0039] Example 3
[0040] The difference between this embodiment and embodiment 1 is that the high-strength aluminum alloy profile for the automobile door sill beam of this embodiment includes the following metal element components in percentage by mass: Zn 5.0%, Mg 1.8%, Zr 2.0%, Cr 0.2%, Ti 0.1%, Cu 0.5%, Mn 0.6%, Si 0.35%, Fe≤0.05%, and the balance is Al.
[0041] Example 4
[0042] The difference between this embodiment and embodiment 1 is that the high-strength aluminum alloy profile for the automobile door sill beam of this embodiment includes the following metal element components in percentage by mass: Zn 4.3%, Mg 1.4%, Zr 1.3%, Cr 0.15%, Ti 0.08%, Cu 0.2%, Mn 0.4%, Si 0.25%, Fe≤0.05%, and the balance is Al.
[0043] Example 5
[0044] The difference between this embodiment and embodiment 1 is that the high-strength aluminum alloy profile for the automobile door sill beam of this embodiment includes the following metal element components in percentage by mass: Zn 4.5%, Mg 1.6%, Zr 1.5%, Cr 0.2%, Ti 0.1%, Cu 0.2%, Mn 0.4%, Si 0.25%, Fe≤0.05%, and the balance is Al.
[0045] Example 6
[0046] The difference between this embodiment and embodiment 1 is that the high-strength aluminum alloy profile for the automobile door sill beam of this embodiment includes the following metal element components in percentage by mass: Zn 4.3%, Mg 1.4%, Zr 1.3%, Cr 0.15%, Ti 0.08%, Cu 0.5%, Mn 0.6%, Si 0.35%, Fe≤0.05%, and the balance is Al.
[0047] Example 7
[0048] The difference between this embodiment and embodiment 1 is that the high-strength aluminum alloy profile for the automobile door sill beam of this embodiment includes the following metal element components in percentage by mass: Zn 4.5%, Mg 1.6%, Zr 1.5%, Cr 0.2%, Ti 0.1%, Cu 0.5%, Mn 0.6%, Si 0.35%, Fe≤0.05%, and the balance is Al.
[0049] Example 8
[0050] The difference between this embodiment and embodiment 1 is that the high-strength aluminum alloy profile for the automobile door sill beam of this embodiment includes the following metal element components in percentage by mass: Zn 4.4%, Mg 1.5%, Zr 1.4%, Cr 0.18%, Ti 0.09%, Cu 0.25%, Mn 0.5%, Si 0.30%, Fe≤0.05%, and the balance is Al.
[0051] Comparative Example 1
[0052] The difference between this comparative example and Example 1 is that the aluminum alloy profile for the automobile door sill beam of this comparative example includes the following metal element components in mass percentage: Zn 3.8%, Mg 1.3%, Zr 0.8%, Cr 0.06%, Ti 0.05%, Cu 0.2%, Mn 0.4%, Si 0.25%, Fe≤0.05%, and the balance is Al.
[0053] Comparative Example 2
[0054] The difference between this comparative example and Example 1 is that the Zn content is different. The Zn content in this comparative example is 3.5%.
[0055] Comparative Example 3
[0056] The difference between this comparative example and Example 1 is that the Zr element content is different. The Zr element content in this comparative example is 0.8%.
[0057] Comparative Example 4
[0058] The difference between this comparative example and Example 1 is that the Cr element content is different. The Cr element content in this comparative example is 0.06%.
[0059] Comparative Example 5
[0060] The difference between this comparative example and Example 1 is that the contents of Zr and Cr elements are different. In this comparative example, the content of Zr element is 0.8%, and the content of Cr element is 0.06%.
[0061] Comparative Example 6
[0062] The difference between this comparative example and Example 1 is that the Mn element content is different. The Mn element content in this comparative example is 0.35%.
[0063] The sill beam profiles prepared in the above-mentioned Examples 1-8 and Comparative Examples 1-6 were sampled and tested for mechanical properties, as shown in Table 1 below.
[0064] Table 1 Mechanical properties of sill beam profiles prepared by online water quenching in Examples 1-8 and Comparative Examples 1-6
[0065] From Table 1 we can see that: Compared with Comparative Examples 1-6, the aluminum alloy profiles prepared within the alloy composition range of Examples 1-8 have high strength and high elongation; Compared with Example 1, when the Zn content is reduced in Comparative Example 2, the strength and elongation of the aluminum alloy profile are significantly reduced; the main reason is that the Zn content in Comparative Example 2 is low, the formed MgZn2 strengthening phase is small, and the residual amount of zinc atoms is also small, resulting in reduced strength and toughness; Compared with Example 1, when the Zr element content is reduced in Comparative Example 3, the elongation of the aluminum alloy profile is significantly reduced and the strength is slightly reduced; the main reason is that the Zr element content in Comparative Example 3 is low, and the Al3Zr dispersed phase formed is reduced, thereby affecting its strength and toughness; Compared with Example 1, when the Cr content in Comparative Example 4 is reduced, the strength and elongation of the aluminum alloy profile are only slightly reduced, and the change is not obvious; since the Cr content in Example 1 is originally low, only a slight reduction in the Cr content has no obvious effect on the change of mechanical properties; Compared with Example 1 and Comparative Example 4, when the Zr element and the Cr element in Comparative Example 5 are both reduced, the strength and elongation of the aluminum alloy profile are significantly reduced; compared with Comparative Example 3, its elongation is significantly reduced; the main reason is that when the Zr and Cr elements are both low, not only the Al3Zr dispersed phase is reduced, but also the combined effect of the two is weakened, and the coherent interface formed between the dispersed phase and the matrix is reduced, thereby affecting its strength and toughness; Compared with Example 1, when the Mn element content is reduced in Comparative Example 6, the strength and elongation of the aluminum alloy profile are only slightly reduced, and the change is not obvious; this is because: the strengthening phase in the aluminum alloy profile of the present invention is mainly MgZn2 phase, the addition amount of Mn element is originally low, and the mechanical properties are not significantly changed by only a slight reduction in the Mn element content; Mn element is a trace added element, which can inhibit matrix recrystallization to a certain extent, prevent grain growth, and thus improve its corrosion resistance.
[0066] In addition, the hardness of Examples 1-8 and Comparative Examples 1 and 2 was tested. The hardness values of Examples 1-8 reached 132-136 HB, and the hardness value of Comparative Examples 1 and 2 was 128 HB.
[0067] In addition, the aluminum bars made of the alloy components of the above-mentioned Examples 1-8 and Comparative Example 1 were extruded according to the same extrusion process, but during quenching, online water mist quenching was adopted, and then they were stretched and sawed by the same stretching process, and then aged according to the same aging system to obtain the threshold beam profile, and samples were taken for mechanical property testing, as shown in Table 2 below.
[0068] Table 2 Mechanical properties of sill beam profiles prepared by online water mist quenching in Examples 1-8 and Comparative Example 1
[0069] Comparing the mechanical properties of Table 1 with those of Table 2, the performance of the aluminum profiles obtained by online water quenching is significantly better than that obtained by online water mist quenching.
[0070] In addition, the aluminum alloy profiles prepared by online water quenching in Example 8 and the aluminum alloy profiles prepared by online water mist quenching in Example 8 were sampled for metallographic examination. The sampling area was the coarse grain ring area, respectively. Figure 1 and Figure 2 As shown, from Figure 1 and Figure 2 It can be seen that: Figure 1 The grains in the metallographic structure are relatively uniform, the width of the coarse grain ring is small, and the coarse grain distribution is small. Figure 2 There are more coarse crystals and the width of the coarse crystal ring is wide, which is also consistent with the results of mechanical properties test. The fine grain structure can significantly improve the mechanical properties of the material.
[0071] It should be noted that some parts not described in the present invention can be implemented by adopting or drawing on existing technologies.
[0072] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A high-strength aluminum alloy profile for automobile door sill beam, characterized in that: The invention comprises the following metal element components in mass percentage: Si 0.25-0.35%, Mg 1.2-1.6%, Cu 0.2-0.5%, Mn 0.4-0.6%, Cr 0.1-0.2%, Fe≤0.05%, Zn 4.0-4.5%, Zr 1.0-1.5%, Ti 0.05-0.1%, and the balance is Al and unavoidable impurities.
2. The high-strength aluminum alloy profile for automobile door sill beam according to claim 1, characterized in that: The invention comprises the following metal element components in mass percentage: Si 0.25-0.35%, Mg 1.4-1.6%, Cu 0.2-0.5%, Mn 0.4-0.6%, Cr 0.15-0.2%, Fe≤0.05%, Zn 4.3-4.5%, Zr 1.3-1.5%, Ti 0.08-0.1%, and the balance is Al and unavoidable impurities.
3. The high-strength aluminum alloy profile for automobile door sill beam according to claim 1, characterized in that: The aluminum alloy profile has a tensile strength of ≥470MPa, a yield strength of ≥430MPa, and an elongation of ≥16%.
4. A method for preparing a high-strength aluminum alloy profile for an automobile door sill beam as claimed in any one of claims 1 to 3, characterized in that: The process includes: melting according to alloy composition → casting aluminum rods → homogenization → extrusion molding → online quenching → stretching → sawing → artificial aging → testing whether the mechanical properties meet the requirements.
5. The method for preparing a high-strength aluminum alloy profile for an automobile door sill beam according to claim 4, characterized in that: In the smelting process, the alkali metals in the aluminum liquid after refining need to be controlled to K≤0.0002%, Na≤0.0002%, and Ca≤0.0005%.
6. The method for preparing a high-strength aluminum alloy profile for an automobile door sill beam according to claim 4, characterized in that: The homogenization process is as follows: the homogenization temperature is 460±3° C., the heat preservation time is 36±0.5 h, and the homogenization is completed and the homogenization is naturally cooled to room temperature.
7. The method for preparing a high-strength aluminum alloy profile for an automobile door sill beam according to claim 4, characterized in that: The specific parameters of the extrusion molding process are: aluminum rod temperature is 500±10°C, extrusion barrel temperature is 440±20°C, mold temperature is 480±15°C, mold heating time is 5~24h, extrusion rod speed is 1.0~1.5mm / s, traction speed is 1.2~1.6m / min, and outlet temperature is 515~540°C.
8. The method for preparing a high-strength aluminum alloy profile for an automobile door sill beam according to claim 4, characterized in that: In the online quenching process, online water quenching is adopted, and the temperature after quenching is ≤60°C.
9. The method for preparing a high-strength aluminum alloy profile for an automobile door sill beam according to claim 4, characterized in that: In the stretching step, the stretching ratio is 2%.
10. The method for preparing a high-strength aluminum alloy profile for an automobile door sill beam according to claim 4, characterized in that: The artificial aging process adopts a double-stage aging process, with the first stage aging being 105±5°C×8h and the second stage aging being 155±5°C×8h.
Citation Information
Patent Citations
Production technology for improving fatigue resistance of special aluminum profile for automobile bearing component and special aluminum profile produced by production technology for automobile bearing component
CN107574343A
High-strength corrosion-resistant 6XXX series aluminum alloys and methods of making same
CN110662852A
Al-Mg-Si alloy profile with low critical quenching rate and high strength as well as preparation method and application of Al-Mg-Si alloy profile
CN118814033A
Casted aluminum alloy and method for producing the same as well as aluminum alloy material and method for producing the same
US20100098580A1
Crashworthy alloy
US20240131586A1
